Distribution and behaviour of reduced sulfur substances in the oligotrophic and hydrothermal waters of the Western Tropical South Pacific - Portlock, Gemma; Whitby, Hannah; Salaün, Pascal (Frontiers in Marine Science, 2024)
Reduced sulfur species (RSS) are involved in essential biological and chemical processes, including metal complexation, yet little is known about their occurrence and behaviour in marine systems. Here, we present a quantitative and qualitative data set of species-specific RSS in open ocean samples collected during the GEOTRACES Tonga GPpr14 cruise. The cruise traversed differing biogeochemical provinces, from the mesotrophic Melanesian waters and the North Fiji Basin, through the hydrothermally active Lau Basin, eastward to the oligotrophic South Pacific Gyre. Using cathodic stripping voltammetry in acidified samples (pH 2), we measured the concentration of two RSS, with peak potentials of -0.18 and -0.09 V in equivalents of thioacetamide (TA) and glutathione (GSH) respectively. GSH-like compounds were only present in the upper 200 m at concentrations up to 6.2 nM eq. GSH, consistent with other cathodic stripping voltammetry as well as chromatography-based studies. In contrast, RSS−0.18 V2 compounds were detected at all depths at concentrations ranging from 48 nM to 980 nM eq. TA. Both RSS−0.18 V2 and GSH-like compounds were present at higher levels in the hydrothermally-impacted region of the Lau Basin relative to other stations. The highest levels, along with high sulfide concentrations, were detected in a hydrothermal plume sample, indicating that hydrothermal vents are a direct or indirect source of these compounds. Elevated levels of RSS−0.18 V2 compounds were detected throughout almost the entire water column at a station located in the North Fiji Basin. We also employed the qualitative technique of cathodic pseudopolarography on unbuffered samples (pH ~ 8.5). Pseudopolarograms of marine RSS were compared to sulfide, GSH and TA standards. Pseudopolarography supports the presence of GSH in marine samples. However, while a compound that is electrochemically similar to TA is often detected in marine samples, TA itself is not thought to be naturally present. This is supported by our pseudopolarograms of RSS−0.52 V8.5 which often lacked the characteristic TA reduction wave but suggested the presence of other unidentified RSS compounds.